TINGKATKAN LAYANAN PERPUSTAKAAN: STUDI KASUS PELATIHAN MENDELEY OLEH MAHASISWA PkM DAN LEMBAGA PERPUSTAKAAN DI UNIVERSITAS MUHAMMADIYAH BENGKULU - Wulandari, Viqe; Putra, Adeyansyah; Abdullah , Dedy (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to explore efforts to improve library services through a case study of Mendeley training conducted by Student Service (PKM) students with library institutions at the University of Muhammadiyah Bengkulu. Mendeley's training aims to improve understanding and utilization of reference management tools in the context of scientific research and writing. This research method uses a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The results showed that Mendeley's training has had a positive impact in improving student competence in reference management and facilitating access to scientific literature. In addition, collaboration between PKM students and library institutions results in synergies that strengthen library services as a whole. This research makes an important contribution in enriching the understanding of service improvement strategies.